Square Wave Electroanalysis at Generator-Collector Gold-Gold Double Hemisphere Junctions - Lewis, G; Dale, S; Kasprzyk-Hordern, B; Barnes, E; Compton, R; Marken, F (2012)
Gold-gold double-hemisphere junction electrodes with an inter-electrode gap of typically 1μm are employed for generator-collector square wave voltammetry. Electrochemical data are recorded as a function of both generator and collector potential to give three-dimensional response "maps". At sufficiently low frequencies, close-to-steady-state conditions for the collector response are achieved and peak responses complementary to those for the generator electrode are recorded. Due to localised interelectrode gap diffusion (fast) as opposed to peripheral diffusion (slow), information about reaction products and intermediates can be obtained. Local pH gradient effects provide additional "fingerprint" information beneficial for future application in analytical detection. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.